The Role of Auditors, Non-Auditors, and Internal Tax Departments in Corporate Tax Aggressiveness - Klassen, Kenneth J.; Lisowsky, Petro; Mescall, Devan (The Accounting Review, 2016)
ABSTRACT Using confidential data from the Internal Revenue Service on who signs a corporation's tax return, we investigate whether the party primarily responsible for the tax compliance function of the firm—the auditor, an external non-auditor, or the internal tax department—is related to the corporation's tax aggressiveness. We report three key findings: (1) firms preparing their own tax returns or hiring a non-auditor claim more aggressive tax positions than firms using their auditor as the tax preparer; (2) auditor-provided tax services are related to tax aggressiveness even after considering tax preparer identity, which supports and extends prior research using tax fees as a proxy for tax planning; and (3) Big 4 tax preparers, in particular, are linked to less tax aggressiveness when they are the auditor than when they are not the auditor. Our findings help policymakers and researchers better understand an important feature of tax compliance intermediaries; particularly, how the dual role via audits is related to observable corporate tax outcomes.